THE ROLE OF HUMANITARIAN COOPERATION IN BRAZILIAN FOREIGN POLICY AS A STRATEGY OF SOFT POWER (2003-2016) - Mello Valença, Marcelo; Bizzo Affonso, Luiza (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Humanitarian cooperation initiatives were central to Brazilian Foreign Policy in the two first decades of the 21st century. Based on national initiatives considered successful, these programs have been used as tools for the country’s projection to achieve an international leadership role. This article explores the role of humanitarian cooperation in Brazilian foreign policy in order to show that, although it was not the only policy developed, it evidenced Brazilian soft power and allowed the country to achieve prominence and place its interests on international agendas.